PERAN MODERASI UKURAN PERUSAHAAN PADA HUBUNGAN PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN PENGUNGKAPAN CSR - Anindyafebi Tanara; Zaky Machmuddah; St. Dwiarso Utomo (Universitas Dian Nuswantoro, 2023)
This research was conducted at the intention of observing and measuring the result of profitability, liquidity and leverage on CSR and company size as a moderating variable. The population taken was 29 manufacturing corporation in the food and beverage area recorded on the IDX in 2018-2021. The sample selection category applied purposive sampling, with a total of 116 samples tested using WarpPLS 7.0 as a research tool. Independent variables include profitability, liquidity, and leverage whereas the dependent variable include CSR and company size as moderating variables. The research results show that ROA and DER have a notable impact on the corporate social explanations. Meanwhile, CR has no impact on the explanation of CSR. Company size could strengthen ROA, CR, and DER in CSR disclosure.Â